Analisis Kemampuan Berpikir Kritis Calon Guru Biologi di Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar - Abd. Muis; Ismail Ismail; Dian Dwi Putri Ulan Sari Patongai (Seminar Nasional LP2M UNM, 2022)
Abstract. Critical thinking skills are something that all prospective teachers need to have, including prospective biology teachers. These skills become provisions for prospective teachers to develop high-level learning and lead to the creation of quality graduates who can adapt to the needs of the globalization era. FMIPA UNM is one of the campuses that prints future teacher candidates, so it is deemed necessary to pay attention to the quality of graduates, one of which is in the aspect of critical thinking skills. The purpose of this research is to analyze the critical thinking skills of prospective biology teachers at the State University of Makassar. This research is descriptive research. The research subjects were prospective biology teachers, FMIPA UNM with a sample of 52 people. Data collection in this study used a research instrument in the form of critical thinking questions on metabolic material that referred to the indicators developed by Ennis (2011). The results showed that the critical thinking skills of prospective biology teachers, Faculty of Mathematics and Natural Sciences, Makassar State University were 67,067 and were in the medium category. The highest average score on the indicator formulating the problem. Keywords: Analysis, Critical Thinking, Prospective Teachers, Biology.